Cd-composition induced effects on structure, optical and electrical properties of sputtered Zn1−xCdxO films. Issue 4 (May 2015) - Sui, Y.R.; Yue, Y.G.; Song, Y.P.; Yao, B.; Cao, Y.; Lang, J.H.; Li, X.Y.; Yang, J.H.
Abstract: Zn1− x Cd x O films with different Cd contents (0≤ x ≤1) were successfully deposited on quartz substrates by the direct current reactive magnetron sputtering and post-annealing techniques. It was found that structures, band gaps and electrical properties of the films can be tuned by changing Cd contents x . The Zn1− x Cd x O film consists of wurtzite phase with highly (002)-preferred orientation at x from 0 to 0.2, mixture of wurtzite and cubic phases at x =0.5, and cubic phase with highly (200)-preferred orientation at x ≥0.8. The band gap decreases from 3.25 eV at x =0 to 2.75 eV at x =0.2 for the wurtzite Zn1− x Cd x O, and decreases from 2.52 eV at x =0.8 to 2.42 eV at x =1, which has a little change for cubic Zn1− x Cd x O. In addition, Hall measurement results indicate that the influence of Cd content on the conduction behavior of Zn1− x Cd x O films is significant. The chemical compositions and the bonding states of Zn1− x Cd x O films were examined by X-ray photoelectron spectroscopy analysis.